Formulation of microfinance institutions sustainability index in Malaysia / Muhammad Saad … [et al.] - Saad, Muhammad; Bhuiyan, Abul Bashar; Ali, Md Jafor; Munir, Abu Naaim; Alias, Zuraini (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Sustainability of Microfinance Institutions (MFIs) has considerably gained the attention of researchers during the past decade. The dual goals social sustainability and financial sustainability of MFIs are widely studied yet remain unsolved in the existing literature. This study has addressed the above gap by developing a composite index of sustainability for MFIs. Data for MFI in Malaysia was used, and Principal Component analysis is applied for obtaining sustainability score. Quantile, Stepwise and Robust Regression analysis are used to identify the determinants of sustainability. Empirical findings suggest that portfolio quality, operating efficiency, leverage, and size influence the sustainability of MFIs in Malaysia. The study is a novel attempt to develop sustainability Index for MFIs in Malaysia. The findings of the study may help both policy makers and practitioners to better understand the dual goal perspective and significant determinants of MFIs sustainability in Malaysia.